Humidity - Schuetz, Kristin (Minneapolis, MN : Bellwether Media, 2016)
"Relevant images match informative text in this introduction to humidity. Intended for students in kindergarten through third grade"--Provided by publisher.
What is humidity? -- Relative humidity -- Dew point -- Why is humidity important?
Includes bibliographical references and index.
005-008.
K to Grade 3.
Keywords: Humidity -- Juvenile literature